2017
DOI: 10.1021/acs.inorgchem.7b00412
|View full text |Cite
|
Sign up to set email alerts
|

Solvent- and DNA-Controlled Phototriggered Linkage Isomerization in a Ruthenium Sulfoxide Complex Incorporating Dipyrido[3,2-a:2′,3′-c]phenazine (dppz)

Abstract: A new tris-heteroleptic complex [Ru(bpy)(dppz)(OSO)](ClO), [1](ClO) (bpy = 2,2'-bipyridine, dppz = dipyrido[3,2-a:2',3'-c]phenazine and OSO = 2-methylsulfinylbenzoate), was synthesized and characterized to control the photochromic Ru-S → Ru-O linkage isomerization. Details isomerization kinetics studied by UV-visible absorption spectroscopy and cyclic voltammetry revealed that efficient photochromic S → O isomerization and thermal O → S reversal take place in solvents like propylene carbonate (PC), methanol, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 73 publications
0
1
0
Order By: Relevance
“…However, it was only partially characterized and no biological studies were ever reported. 60,61 High-resolution mass spectrometry showed a peak at m/z of 575.0331 with a typical isotopic abundance of ruthenium that corresponded to the [Ru(bpy)(dppz)Cl] + ion (theoretical m/z = 575.0325), supporting the presence of both distinct chelating ligands. Further characterizations were consistent with the formulation, as shown in the ESI (Fig.…”
Section: Characterization Of the Metal Compoundsmentioning
confidence: 93%
“…However, it was only partially characterized and no biological studies were ever reported. 60,61 High-resolution mass spectrometry showed a peak at m/z of 575.0331 with a typical isotopic abundance of ruthenium that corresponded to the [Ru(bpy)(dppz)Cl] + ion (theoretical m/z = 575.0325), supporting the presence of both distinct chelating ligands. Further characterizations were consistent with the formulation, as shown in the ESI (Fig.…”
Section: Characterization Of the Metal Compoundsmentioning
confidence: 93%